Desaturation-Distance Ratio During Submaximal and Maximal Exercise Tests and Its Association With Lung Function Parameters in Patients With Lymphangioleiomyomatosis - Queiroz, Douglas Silva; da Silva, Cibele Cristine Berto Marques; Amaral, Alexandre Franco; Oliveira, Martina Rodrigues; Moriya, Henrique Takachi; Carvalho, Carlos Roberto Ribeiro; Baldi, Bruno Guedes; Carvalho, Celso R. F. (Frontiers in Medicine, 2021)
Background: The desaturation-distance ratio (DDR), which is the ratio of the desaturation area to the distance walked, is a promising, reliable, and simple physiologic tool for functional evaluation in subjects with interstitial lung diseases. Lymphangioleiomyomatosis (LAM) is a rare neoplastic condition frequently associated with exercise impairment. However, DDR has rarely been evaluated in patients with LAM. Objectives: To assess DDR during maximal and submaximal exercises and evaluate whether DDR can be predicted using lung function parameters. Methods: A cross-sectional study was conducted in a cohort of women with LAM. The six-minute walking test (6MWT) and the incremental shuttle walking test (ISWT) were performed, and DDR was obtained from both tests. The functional parameters were assessed at rest using spirometry and body plethysmography. The pulmonary function variables predictive of DDR were also assessed. Results: Forty patients were included in this study. The mean age was 46 ± 10 years. Airway obstruction, reduced DLCO, and air trapping were found in 60%, 57%, and 15% of patients, respectively. The distance walked and DDR were 517±65m and 443±127 m; and 6.6(3.8-10.9) and 8.3(6.2-12.7) for the 6MWT and ISWT, respectively. FEV1 (airway obstruction), reduced DLCO and RV/TLC (air trapping) were independent variables predictive of DDR during submaximal (DDR6MWT=18.66–(0.06*FEV1)–(0.10*DLCO)+(1.54*RV/TLC), R2adjust=0.43) and maximal (DDRISWT =18.84–(0.09*FEV1)–(0.05*DLCO)+(3.10*RV/TLC), R2adjust=0.33) exercises. Conclusion: Our results demonstrated that DDR is a useful tool for functional evaluation during maximal and submaximal exercise in patients with LAM, and it can be predicted using airway obstruction, diffusion capacity, and air trapping.